Visualizing Ice Quality on Lake Mendota - Jing, Aaron; Murray, Regan; Olson, Blake (My University, 2019)
We examined the quality of ice health on Lake Mendota because of the lack of an easy-to-understand resource visualizing how climate change will impact the local culture and lake ecology in Madison. We assessed ice duration from 1870-2015 and ice thickness from 1870-2018 by evaluating a pre-existing dataset for ice duration and created a new one for thickness derived from the LIMNOS ice model. We discovered that both ice thickness and duration of ice cover on Lake Mendota are on a steady decline. As a result of this decline, we observed a deprecation of cultural history and lake ecology and we expect this trend to continue. Through our interactive map, we hope to educate the local community about the repercussions of climate change in their own backyard and to promote visual aids in representing complicated and technical scientific writing for the general public.
Includes Photographs, Figures, Equations, Images, Graphs, Tables, Appendix and Bibliography.
Keywords: Lake ice; Lake Mendota; Visualization; Ice quality; Climate change